A Runx1-Smad6 Rheostat Controls Runx1 Activity during Embryonic Hematopoiesis - Knezevic, Kathy (American Society for Microbiology, 2011)
The oncogenic transcription factor Runx1 is required for the specification of definitive hematopoietic stem cells (HSC) in the developing embryo. The activity of this master regulator is tightly controlled during development. The transcription factors that upregulate the expression of Runx1 also upregulate the expression of Smad6, the inhibitory Smad, which controls Runx1 activity by targeting it to the proteasome. Here we show that Runx1, in conjunction with Fli1, Gata2, and Scl, directly regulates the expression of Smad6 in the aorta-gonad-mesonephros (AGM) region in the developing embryo, where HSCs originate. Runx1 regulates Smad6 activity via a novel upstream enhancer, and Runx1 null embryos show reduced Smad6 transcripts in the yolk-sac and c-Kit-positive fetal liver cells. By directly regulating the expression of Smad6, Runx1 sets up a functional rheostat to control its own activity. The perturbation of this rheostat, using a proteasomal inhibitor, results in an increase in Runx1 and Smad6 levels that can be directly attributed to increased Runx1 binding to tissue-specific regulatory elements of these genes. Taken together, we describe a scenario in which a key hematopoietic transcription factor controls its own expression levels by transcriptionally controlling its controller.